Time-of-Day Effect on Hip Flexibility Associated with the Modified Sit-and- Reach Test in Males - Guariglia, D. A.; Pereira, L. M.; Dias, J. M.; Pereira, H. M.; Menacho, M. O.; Silva, D. A.; Cyrino, E. S.; Cardoso, J. R. (International Journal of Sports Medicine, 2011)
Flexibility is a key component of physical fitness. It has been suggested that measures of physical fitness components may vary throughout the day. The aim of this study was to analyse the effects of the time of day on flexibility performance. 26 men (mean age=25.4 years, SD=2.5) were evaluated by hip flexion on kinematic analysis and also by an absolute score in the modified Sit-and-Reach test during a repeated measure design. This was done during 3 experimental sessions, which took place at 8:00 a.m., 1:00 p.m. and 6:00 p.m., in random order. All subjects were previously familiarized with the test parameters. There was a diurnal variation only in the modified Sit-and-Reach test score between 8:00 a.m and 6:00 p.m. (P=0.01). There was no significant difference in the hip kinematic analysis between hours. These findings suggest that flexibility performance in the modified Sit-and-Reach test, in absolute scores, is affected by the time of day, with higher performance in the evening.
Keywords: range of motion; circadian rhythm; performance